2022
DOI: 10.1021/acs.biomac.1c01428
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Bilayer Hydrogel for Wound Dressing through PET-RAFT Polymerization

Abstract: Multifunctional hydrogel-based wound dressings have been explored for decades due to their huge potential in multifaceted medical intervention to wound healing. However, it is usually not easy to fabricate a single hydrogel with all of the desirable functions at one time. Herein, a bilayer model with an outer layer for hydrogel wound dressing was proposed. The inner layer (Hm-PNn) was a hybrid hydrogel prepared by N-isopropylacrylamide and chitosan-N-2-hydroxypropyl trimethylammonium chloride (HACC), and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…; which may cause concern in biomedical application. A few recent investigations were reported on PNIPAM-based copolymeric hydrogel systems, e.g., Laponite ® platelets/PNIPAM hydrogel [ 162 ], polypyrrole/PNIPAM hydrogel [ 163 ], polyethylene glycol diacrylate (PEGDA)/chitosan (CS)/PNIPAM hydrogel [ 164 ], chitosan– N -2-hydroxypropyl trimethylammonium chloride (HACC)/PNIPAM hydrogel [ 165 ] etc. ; where biological properties and mechanical properties were improved.…”
Section: Formulation Approaches For Tailoring the Mechanical Behavior...mentioning
confidence: 99%
“…; which may cause concern in biomedical application. A few recent investigations were reported on PNIPAM-based copolymeric hydrogel systems, e.g., Laponite ® platelets/PNIPAM hydrogel [ 162 ], polypyrrole/PNIPAM hydrogel [ 163 ], polyethylene glycol diacrylate (PEGDA)/chitosan (CS)/PNIPAM hydrogel [ 164 ], chitosan– N -2-hydroxypropyl trimethylammonium chloride (HACC)/PNIPAM hydrogel [ 165 ] etc. ; where biological properties and mechanical properties were improved.…”
Section: Formulation Approaches For Tailoring the Mechanical Behavior...mentioning
confidence: 99%
“…A hydrogel’s antibacterial resistance can be exhibited without drugs by the modification of polymers [ 125 ]. A bilayer hydrogel material consisting of N-isopropylacrylamide and a chitosan-N-2-hydroxypropyltrimethylammonium chloride (HACC) inner layer (Hm-PNn) and a polyvinyl alcohol and acrylamide outer layer (PVAo-PAmp) was covalently crosslinked by the photoinduced electron/energy transfer polymerization-reversible addition-fragmentation with chain transfer (PET-RAFT).…”
Section: Biomedical Application Of Bilayer Hydrogelsmentioning
confidence: 99%
“…The inner polymer layer consisting of chitosan- N -2-hydroxypropyl trimethylammonium chloride- co -poly(NIPAM) was synthesized first, with the RAFT process permitting subsequent chain extension to form the outer layer consisting of poly(vinyl alcohol)- co -polyacrylamide. Freeze–thaw cycles resulted in PVA crystallization and physical crosslinking to strengthen the outer layer [ 162 ]. Wu et al demonstrated the versatility of PET-RAFT with a novel organic photocatalyst designed based on density functional theory studies.…”
Section: Synthesis Strategies To Achieve Target Propertiesmentioning
confidence: 99%